WIRELESS SENSOR NETWORKS FOR PRECISION AGRICULTURE: ENHANCING CROP NUTRITION THROUGH SMART COMMUNICATION TECHNOLOGIES (International Journal of Food and Nutritional Sciences, 2021)
Abstract: Precision agriculture is increasingly benefiting from advancements in technology, particularly through the use of Wireless Sensor Networks (WSNs) and smart communication technologies. This paper explores how WSNs, which consist of distributed sensors communicating wirelessly, enhance crop nutrition and optimize agricultural practices. By providing real-time data on soil moisture, nutrient levels, and environmental conditions, WSNs enable precise management of resources, leading to improved crop health and yield. The integration of smart communication technologies, such as IoT and AI, further enhances the effectiveness of WSNs by enabling seamless data collection, advanced analytics, and automated decision-making. This study examines the application of WSNs in precision agriculture, highlighting their impact on resource efficiency, cost savings, and overall farm productivity. It also addresses challenges such as data accuracy, network reliability, and implementation costs, offering solutions and future directions for research and development. Through case studies and real-world examples, this paper demonstrates the transformative potential of WSNs in modern agriculture, emphasizing their role in advancing sustainable farming practices and achieving greater food security.